Perceived National Health Insurance Financial Compensation and Employee Performance in Primary Health Care: A Cross-Sectional Study - Husnul Khotimah; Firasatul Ulum; Joko Prananto (Genius Journal of Nursing, 2026)
Background: Financial compensation is an important factor in human resource management because it may influence employee motivation and performance. In Indonesian primary health care, National Health Insurance capitation funds are used partly for service incentives, but employees may have different perceptions of their fairness and appropriateness. Objectives:  This study aimed to analyze the association between perceived National Health Insurance financial compensation and employee performance in primary health care. Methods: This study used a correlational analytic design with a cross-sectional approach. A total of 37 employees from a public primary health care centre were included using total population sampling. Perceived National Health Insurance financial compensation and employee performance were measured using structured questionnaires. Data were analyzed using descriptive statistics and Spearman’s rho correlation test. Results: Most respondents disagreed with the distribution of financial compensation (51.4%), and most had moderate performance (62.1%). Spearman’s rho analysis showed a significant positive association between perceived financial compensation and employee performance (r = 0.391; p = 0.017). Conclusions: Perceived National Health Insurance financial compensation was significantly associated with employee performance. Fair, transparent, and performance-oriented compensation management may help strengthen employee motivation and service quality in primary health care.